Newly Developed Anti-Dandruff Regimen, VB-3222, Delivers Enhanced Sensorial and Effective Therapeutic Benefits Against Moderate Adherent Dandruff - Sadhasivam S; Garkhal K; Singh H; Yadav V; Chawrai S; Ramnane M; Jain S; Sardana K; Ghosh S (Dove Medical Press, 2020)
Suresh Sadhasivam,1 Kalpna Garkhal,1 Himanshi Singh,1 Vishal Yadav,1 Suresh Chawrai,1 Mukesh Ramnane,2 Shilpi Jain,1 Kabir Sardana,3 Shamik Ghosh1 1Vyome Therapeutics Limited, New Delhi 110092, India; 2MS Clinical Research Pvt. Ltd, Ulsoor, Bangalore 560008, India; 3Department of Dermatology, Dr RML Hospital and PGIMER, New Delhi 110001, IndiaCorrespondence: Shamik GhoshVyome Therapeutics Limited, 465 Ground Floor, Patparganj Industrial Area, New Delhi 110092, IndiaEmail shamik.ghosh@vyometx.comKabir SardanaDepartment of Dermatology, Dr. RML Hospital and PGIMER, New Delhi 110001, IndiaEmail article.sardana@gmail.comBackground: Uninhibited proliferation of Malassezia spp., enhanced sebaceous gland activity and individual sensitivity are three prime etiological factors behind dandruff. For many dandruff sufferers, existing anti-dandruff products start yielding unsatisfactory results after a few cycles of use. This observation made us explore the physical and biological environment of the host and exploit the specific type of lipid dependence of Malassezia spp. for their survival. A shampoo formulation (product code VB-3222) was developed to address the shortcomings of existing therapy.Purpose: Evaluating efficacy of VB-3222 in comparison to marketed products through  in vitro assays and subsequently demonstrating its advantages in a clinical study.Methods: VB-3222 was developed with a derivative of medium chain fatty acid (MCFA) and zinc pyrithione and compared against marketed comparators by in vitro time kill assay. Subsequently, VB-3222 shampoo was tested in a 21-day clinical trial on 25 moderate dandruff subjects to evaluate local safety and efficacy.Results: VB-3222 in all in vitro cases demonstrated significantly better fungicidal activity than its marketed comparators. In the clinical trial, VB-3222 was well tolerated in all subjects and imparted consistent reduction of the ASFS (adherent scalp flaking score) and the pruritus score. At days 7 and 21, 55% and 90% reduction in the ASFS in comparison to treatment initiation and 50% and 95.5% reduction in the pruritus score were observed.Conclusion: The increased efficacy of VB-3222 over comparator products in vitro, and the dramatic reduction (> 90%) in ASFS and pruritis in subjects within 21 days of use with excellent tolerability and sensorial profile, positions VB-3222 as the new generation treatment for adherent dandruff.Clinical Trial Registration No: CTRI/2018/05/013567.Keywords: anti-dandruff shampoo, Malassezia spp., potentiator, dandruff, seborrheic dermatitis